Estudio sobre la determinación temporal del ser en Aristóteles - Rodríguez, Mirtha (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Filosofía., 2005)

(untitled)
In order to defíne Time and in ways to rebound its essence in the "Physica" of Aristotle, the “number" is detached as a unifying principie. The relation “number" - “now" is the key in the interpretation of time.